Public Contracts as Accountability Mechanisms: Assuring quality in public health care in England and Wales. Issue 1 (2nd January 2016) - Allen, Pauline; Hughes, David; Vincent-Jones, Peter; Petsoulas, Christina; Doheny, Shane; Roberts, Jennifer A.
Abstract: Contracting in the public sector is designed to enhance the accountability of service providers to their funders. The idea is that quality is improved by the use of service specifications, monitoring of performance and imposition of contractual sanctions. Socio-legal and economic theories of contract indicate that it will be difficult to make and enforce contracts to achieve this. The results of a study of National Health Services contracting in England and Wales are reported. We conclude that contracts alone are not sufficient to improve accountability – collibration of various regulatory measures (including more hierarchical mechanisms such as performance targets) is required.